Peningkatan Kemampuan Kader Kesehatan dalam Penerapan Akupresur untuk Mengatasi Emesis Gravidarum - Rudiyanti, Novita; Nurchairina, Nurchairina; Octaviana, Amrina (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2021)
Efforts to prevent Chronic Energy Deficiency in pregnant women and low birth weight are quality ANC services and balanced nutritional intake. In early pregnancy, the formation of fetal organs and preparation of the mother's body requires good nutrition. However, at the beginning of pregnancy, there is emesis gravidarum which causes the mother to not be able to consume food to its full potential. As a result, lack of nutritional intake to support fetal and physical growth of the mother. If left unchecked, Chronic Energy Deficiency and low birth weight can occur. The goal is to help mothers reduce nausea and vomiting so they can consume nutritious food to the maximum. The target of the activity is 70 Health Cadres from 12 Posyandu at Karang Anyar Health Center. The method of implementing the activities includes screening, counseling, simulation, practice and discussion about emesis gravidarum and acupressure, followed by the practice of doing acupressure for all cadres until they are able to independently. At the beginning, a pre-test was carried out and at the end a post-test was carried out. The test results showed an increase with the average pre-test score of 52.3% participants and post-test results the average value of participants was 92.7% and the results of the skill checklist assessment showed all good scores. A follow-up evaluation was carried out on the implementation of the posyandu in the following month, it was found that the cadres had applied acupressure to treat nausea and vomiting in several pregnant women and those around them. The ability of cadres to increase in the application of acupressure to overcome emesis gravidarum and most pregnant women experience a decrease in nausea and vomiting. It is hoped that in the future the cadres will apply their knowledge and skills in a sustainable manner when providing services at the posyandu AbstrakUpaya pencegahan KEK pada ibu hamil dan BBLR yaitu pelayanan ANC yang berkualitas dan asupan gizi seimbang. Diawal kehamilan , pembentukan organ janin dan persiapan tubuh ibu membutuhkan asupan gizi yang baik. Namun diawal kehamilan terjadi emesis gravidarum yang menyebabkan ibu tidak dapat mengkonsumsi makanan secara maksimal. Dampaknya, asupan gizi kurang untuk mensuport pertumbuhaan janin dan fisik ibu. Jika dibiarkan dapat terjadi KEK dan BBLR. Tujuannya membantu ibu mengurangi mual muntah sehingga dapat mengkonsumsi makanan bergizi dengan maksimal. Sasaran kegiatan yaitu Kader Kesehatan berjumlah 70 orang dari 12 Posyandu di Puskesmas Karang Anyar. Metode pelaksanaan kegiatan meliputi screening, penyuluhan, simulasi , prakteik dan diskusi tentang emesis gravidarum dan akupresure dilanjutkan praktek melakukan akupresur bagi seluruh kader sampai mampu secara mandiri. Diawal dilakukan pre test dan diakhir dilakukan post tes. Hasil tes terlihat kenaikan dengan nilai rata-rata pre tes peserta 52,3% dan hasil post test nilai rata-rata peserta 92,7% serta hasil penilaian daftar tilik ketrampilan menunjukan nilai baik semua. Evaluasi lanjutan dilakukan pada pelaksanaan posyandu di bulan berikutnya didapatkan kader telah menerapkan akupresure untuk mengatasi mual muntah pada beberapa ibu hamil dan orang disekitarnya. Kemampuan kader meningkat dalam penerapan akupresur untuk mengatasi emesis gravidarum dan sebagian besar ibu hamil mengalami penurunan mual muntah. Diharapkan kedepan kader menerapakan ilmu dan ketrampilannya secara berkelanjutan pada saat memberikan pelayanan di posyandu.